A new feasible approach based on utility of ninhydrin for selective fluorimetric analysis of baclofen. Application to content uniformity evaluation. (24th November 2020) - Abu‐hassan, Ahmed A.; Ali, Ramadan; Derayea, Sayed M.
Abstract: In the current proposed analysis, a new, feasible, and selective fluorimetric approach was designed for baclofen assay. Baclofen is a medication prescribed as a therapy for muscle spasticity that originated from multiple sclerosis or a spinal cord injury, and other cases such as hiccups. The analytical approach relies on the use of ninhydrin to form a fluorescent derivative that was monitored at λex 386 nm or λem 480 nm. Under suitable reaction conditions, the primary amino moiety in baclofen was condensed with ninhydrin and phenylacetaldehyde in the presence of Teorel buffer as a buffered medium. The method exhibited linearity when baclofen concentration was plotted against response in the range 1–10 μg ml −1 . Adjustment of the reaction variables and study of validation parameters according to ICH directives were performed correctly. An interference study was implemented to ensure that no discrepancy from the excipient had occurred. Finally, the proposed method was applied successfully for baclofen assay in dosage form and extended to test Mylobac content uniformity. Abstract : Simple, accurate, and non‐extractive spectrofluorimetric method for the determination of baclofen. The method depends on condensation with ninhydrin and formation of a fluorescent derivative. The methods were applied successfully for the dosage form and content uniformity test. The method was validated and applied according to the instructions from ICH and the USP.